Antinociceptive Effect of Some Biuret Derivatives on Formalin Test in Mice - Neda Adibpour; Ali Poornajjari; Mohammad Javad Khodayar; Saeed Rezaee (Tabriz University of Medical Sciences, 2014)
Purpose: The current study was designed to investigate the antinociceptive effects of several biuret derivatives with N, N`-diphenyl, N-phenyl-N`-alkylphenyl, N,N`-bis alkylphenyl, 2-methylquinoline-4-yl, benzo[d]thiazol-2-ylthio and (1-phenyl-1H-tetrazol-5-yl)thio substituents on the formalin-evoked pain in mice. Methods: Antinociceptive activity of the nine biurets derivatives were assessed at different doses in mice using formalin test and the results were compared with those of indomethacin(20 mg/kg) and vehicle of the compounds. Area under the pain score curve against time (AUEC) up to 60 minutes was used as the measure of pain behavior. Results: A rather good analgesic effect was seen for most of the tested biuret derivatives. Significant reduction in median AUEC0-5 minutes was observed at the doses of 50 and 25 mg/kg for biurets with either benzyl and 2-methylquinoline-4-yl (C8) or phenylethyl and benzo[d]thiazol-2-ylthio(C9) moieties, respectively(p-value<0.0044). Antinociceptive activities of compound C7 (with bis phenylropyl substituent), C8 and C9 during the late phase of formaldehyde-induced pain were comparable to that of indomethacin. Conclusion: Unlike indomethacin, the tested biuret compounds are able to induce antinociception in both phases of formalin test and could be considered comparable to indomethacin at the selected doses.